The Social Life of the Early Modern Protestant Clergy. - Eales, Jackie; Tjerngren, Beverly (Univ of Wales Press, 2021)
This study uses English and Swedish sources to illustrate the importance of clerical marriage to the success of the Reformation, and examines the social standing of the clergy through their material wealth and financial networks.